Cytisine exerts anti-tumour effects on lung cancer cells by modulating reactive oxygen species-mediated signalling pathways - Wan-Ting Xu; Tian-Zhu Li; Shu-Mei Li; Cheng Wang; Hao Wang; Ying-Hua Luo; Xian-Ji Piao; Jia-Ru Wang; Yu Zhang; Tong Zhang; Hui Xue; Long-Kui Cao; et al. (Artificial Cells, Nanomedicine, and Biotechnology)
Cytisine is a natural product isolated from plants and is a member of the quinolizidine alkaloid family. This study aims to investigate the effect of cytisine in human lung cancer. Cell viability was determined using the CCK-8 assay, and the results showed that cytisine inhibited the growth of lung cancer cell lines. The apoptotic effects were evaluated using flow cytometry, and the results showed that cytisine induced mitochondrial-dependent apoptosis through loss of the mitochondrial membrane potential; increased expression of BAD, cleaved caspase-3, and cleaved-PARP; and decreased expression levels of Bcl-2, pro-caspase-3, and pro-PARP. In addition, cytisine caused G2/M phase cell cycle arrest that was associated with inhibiting the AKT signalling pathway. During apoptosis, cytisine increased the phosphorylation levels of JNK, p38, and I-κB, and decreased the phosphorylation levels of ERK, STAT3, and NF-κB. Furthermore, cytisine treatment led to the generation of ROS, and the NAC attenuated cytisine-induced apoptosis. In vivo, cytisine administration significantly inhibited the lung cancer cell xenograft tumorigenesis. In conclusion, cytisine plays a critical role in suppressing the carcinogenesis of lung cancer cells through cell cycle arrest and induction of mitochondria-mediated apoptosis, suggesting that it may be a promising candidate for the treatment of human lung cancer.